Development of Piezoelectric Energy Harvesting System based on Pressure from Footsteps - Syed Yusof, Syarifah Nur Afrina; Abdullah, Mohd Noor (Evolution in Electrical and Electronic Engineering, 2023)
Electricity is essential and becoming more popular in the present era. The primary source of electricity is fossil fuels, and it is depleting and releasing large amounts of carbon dioxide (CO2) into the atmosphere. Therefore, global energy has shifted from conventional energy to renewable energy sources. The eco-friendly forms of electricity can now be generated by harnessing the energy generated by humans. That energy can be harvested using piezoelectric material. Thus, the primary objective of this project is to design piezoelectric energy harvesting systems based on pressure from footsteps. The mechanism of this system is to convert the mechanical or kinetic energy produced by humans into electrical energy. The system is focused on harvesting low-level energy in the range of microwatts to milliwatts. AC-DC converter circuit is needed in this system to generate DC voltage output because piezoelectric generates AC voltage. This project will use piezoelectric ceramic material with a full-wave bridge rectifier as an AC-DC rectifier circuit. This project is a model for an inexpensive and pollution-free energy harvesting system that uses piezoelectric transducers. The combinations of the full-wave bridge rectifier and DC-DC boost converter effectively increase the output DC voltage. The output voltage generated from the converter is then stored in the rechargeable battery that serves as a storage device. Therefore, the proposed design of the system must be able to generate electricity and able to charge the 12 V lead acid battery. For future recommendations, the number of piezoelectric transducers should be added to result in better performance.